IMPROVING THE QUALITY OF PASSENGER AND FREIGHT TRANSPORTATION OFJSC - Yakhshikulova Mokhinur Tokhir Kizi; Turopov Sardorjon Sheraliyevich (International Journal of Innovations in Engineering Research and Technology, 2021)
Rail passenger transport is the main form of safe transport for traveling long and medium distances. Rail transport is one of the largest sectors of the national economy with complex and diverse equipment and technology, as well as a specific organization and management system.